Molecular coevolution within a Drosophila clock gene. - Peixoto, A.A.; Hennessy, J.M.; Townson, I.; Hasan, G.; Rosbash, M.; Costa, R.; Kyriacou, C.P. (Proceedings of the National Academy of Sciences of the United States of America, 1998)
The period (per) gene in Drosophila melanogaster provides an integral component of biological rhythmicity and encodes a protein that includes a repetitive threonine-glycine (Thr-Gly) tract. Similar repeats are found in the frq and wc2 clock genes of Neurospora crassa and in the mammalian per homologues, but their circadian functions are unknown. In Drosophilids, the length of the Thr-Gly repeat varies widely between species, and sequence comparisons have suggested that the repeat length coevolves with the immediately flanking amino acids. A functional test of the coevolution hypothesis was performed by generating several hybrid per transgenes between Drosophila pseudoobscura and D. melanogaster, whose repetitive regions differ in length by about 150 amino acids. The positions of the chimeric junctions were slightly altered in each transgene. Transformants carrying per constructs in which the repeat of one species was juxtaposed next to the flanking region of the other were almost arrhythmic or showed a striking temperature sensitivity of the circadian period. In contrast, transgenes in which the repeat and flanking regions were conspecific gave wild-type levels of circadian rescue. These results support the coevolutionary interpretation of the interspecific sequence changes in this region of the PER molecule and reveal a functional dimension to this process related to the clock's temperature compensation.